Overview of Anxiety Levels in Pulmonary Tuberculosis Patients in the Working Area of the Pekauman Banjarmasin Health Center - Ruriyanty. R, Nurul Rizka; Irawan, Angga; Rahman, Subhannur (Universitas Ibn Khaldun Bogor, 2025)
Pulmonary tuberculosis is a disease that significantly contributes to global mortality rates, causing worry or fear among sufferers, which can manifest as anxiety. This study aims to determine the level of anxiety of pulmonary tuberculosis sufferers in the Pekauman Health Center area, Banjarmasin. This study aims to assess the level of anxiety among pulmonary tuberculosis sufferers in the Pekauman Health Center area of Banjarmasin. A descriptive survey method with a cross-sectional approach was employed for the research. The sample comprised 36 pulmonary tuberculosis patients selected using total sampling. The instrument utilized in this study was the Hamilton Anxiety Rating Scale (HARS) questionnaire. The results showed that most respondents were male (55.6%), adults (83.3%), had high school education (36.1%), worked privately (44.4%), earned below the minimum wage (58.3%), had no family history of TB (77.8%), and had suffered from TB for more than 2 months (52.8%). The level of anxiety of most respondents, namely 19 out of 36 respondents (52.8%) was classified as moderate. Family support is very important during the treatment process to help reduce the anxiety of pulmonary tuberculosis patients.